MOTIVASI MAHASISWA UNIVERSITAS UDAYANA BEKERJA PARUH WAKTU SEBAGAI OJEK ONLINE - Wahyu, Faisal; Kebayantini, Ni Luh Nyoman; Mahadewi, Ni Made Anggita Sastri (JURNAL ILMIAH SOSIOLOGI (SOROT), 2020)
This study aims to determine the motivation that exists in a Udayana University student who undertakes a part-time job as an online motorcycle taxi. This study uses a qualitative approach with descriptive and explanative types with data collection techniques, observation, interviews and documentation. Analyzed by going through four stages, namely: data collection, data reduction, data presentation, and drawing conclusions. As for the results of this study, there is motivation in a student who studies while working as an online motorcycle taxi, both intrinsically, namely fulfilling personal needs and self-actualization and extrinsic to alleviate family economic problems and work ethic. Based on the theory used, namely social exchange from George C. Homans, then all behavior in student motivation always considers rewards and costs, and is divided into several propositions, namely success propositions, value propositions, approval-aggression propositions, and rationality propositions. Keywords: Motivation, College Student, Online Motorcycle Taxi, Social Exchange